Climate Change and Media Policy Nexus: Opportunities, Challenges, and Policy Recommendations. Case Study of Pakistan - Tanveer Nasir; Sultan Mahmood; Kashmala Ali; Muhammad Abubakar (Dialogue Social Science Review (DSSR), 2025)
Climate change is an immediate global concern, and Pakistan is among the most vulnerable countries to its effects. Media now occupies a prime position in influencing public opinion, policy making, and awareness rising on climate issues. Nevertheless, the reciprocal and dynamic nexus of media and policy making remains under research within the Pakistani setting. The goal of this research is to explore the link between media coverage and climate change policy in Pakistan focusing on challenges and opportunities created by the two. Three specific goals, three questions of research and three hypotheses inform the research, test its hypotheses to assess the effectiveness and role playing by the media in forming climate policies. A quantitative study design is utilizing the survey technique to obtain access to a population of climate change researchers, activists, and professionals. 100 individuals are purposely sample in order to select respondents with relevant expertise. Data is gathered with a structured questionnaire and is presented using descriptive statistics and presented as pie charts to enable easy presentation of trends and respondents' perceptions. Early observations are that while the media has contributed to sensitizing the public, its direct effect on policy reforms is still constrained by institutional, political, and communication gaps. The participants underscored the need for evidence based reporting and enhanced collaboration between media institutions and policy stakeholders. The study concludes that enhanced strategic use of media can assist climate governance in Pakistan by bridging the gap between scientific debate, public awareness, and policy response. Policy suggestions are to enhance journalist training on climate issues, develop fact-based media campaigns, and integrate media actors into national climate policy frameworks.